Abelard’s Ontology of Forms: Some New Evidence from the Nominales and the Albricani - Hansen Heine (Open Philosophy)
This article concerns existents as a contentious issue in contemporary Abelardian scholarship. More precisely, it concerns the ontological standing of forms in Abelard’s metaphysics. Take, for example, the apple on my desk. What ontological standing does its redness have? Is it an actual entity over and above the apple or is it in some sense “reducible” to it? Abelard, famously, was a nominalist, so the question is not about some purported universal redness. Rather, it is about the particular redness of the particular apple on my desk. The issue is contentious in that the best current accounts of Abelard’s metaphysics disagree strongly about how to answer this question. Here, rather than focusing on Abelard’s own writings – which so far have yielded no definitive answer – I will consider some anonymously transmitted and mainly unedited logical texts from the twelfth century and show how his contemporaries understood Abelard’s view and how the followers of his philosophical nemesis, Alberic of Paris, reacted to it.